2011
DOI: 10.1097/eja.0b013e32834bea2a
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial oxidative stress protection by sevoflurane vs. propofol

Abstract: In patients undergoing off-pump CABG, sevoflurane showed better antioxidative properties than propofol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…Finally, it has been suggested that certain anesthesia agents can exert antioxidant activity. Ballester et al recently reported a study comparing the effect of the anaesthetics sevoflurane and propofol on F 2 -IsoP levels in blood samples taken from the coronary sinus of 38 patients undergoing elective off-pump CABG surgery [136]. Interestingly, F 2 -IsoPs did not increase in the patients on sevoflurane while signifi-cant increases were noted in the group who received propofol.…”
Section: Isoprostanes As Biomarkers Of Oxidative Stress In Human Dmentioning
confidence: 99%
“…Finally, it has been suggested that certain anesthesia agents can exert antioxidant activity. Ballester et al recently reported a study comparing the effect of the anaesthetics sevoflurane and propofol on F 2 -IsoP levels in blood samples taken from the coronary sinus of 38 patients undergoing elective off-pump CABG surgery [136]. Interestingly, F 2 -IsoPs did not increase in the patients on sevoflurane while signifi-cant increases were noted in the group who received propofol.…”
Section: Isoprostanes As Biomarkers Of Oxidative Stress In Human Dmentioning
confidence: 99%
“…In contrast to Wang et al., who demonstrated a cardioprotective effect of sevoflurane during CABG without CPB [ 103 ], five other study groups did not observe a similar effect [ 107 , 108 , 113 , 114 , 117 ]. Three of these trials recruited small numbers of patients with n = 18, [ 107 ], n = 20 [ 108 ] and n = 38 [ 114 ], which may have contributed to the negative results, as they are likely to have been statistically underpowered. In addition, the relatively short duration of ischaemia during CABG without CPB, and the low doses of sevoflurane used, may have contributed to the confounding results.…”
Section: Clinical Evidence Of Anaesthetic Preconditioningmentioning
confidence: 58%
“…If the anoxic condition is maintained for long, cellular dysfunction occurs as a result of decreased adenosine 5′ phosphate supply and the resultant changes in the internal environment homeostasis lead to structural damage to cardiomyocytes. The damage to cardiomyocytes has been attributed to several pathophysiological processes, including oxidative stress (15), overactivated inflammatory responses (16,17) and calcium overload (18) in the plasma of the cardiomyocytes. Therefore, interventional strategies targeting these processes may help identify cardioprotective agents that may be useful for administration during the procedures of CPB and open-heart cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%